2016
DOI: 10.4240/wjgs.v8.i11.735
|View full text |Cite
|
Sign up to set email alerts
|

Impact of laparoscopic surgery training laboratory on surgeon's performance

Abstract: Minimally invasive surgery has been replacing the open standard technique in several procedures. Similar or even better postoperative outcomes have been described in laparoscopic or robot-assisted procedures when compared to open surgery. Moreover, minimally invasive surgery has been providing less postoperative pain, shorter hospitalization, and thus a faster return to daily activities. However, the learning curve required to obtain laparoscopic expertise has been a barrier in laparoscopic spreading. Laparosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 52 publications
1
40
0
Order By: Relevance
“…Participants were provided the statements in column 1 prior to starting the course . They were asked to answer on a 5 point scale from strongly agree (1) to strongly disagree (5). Those who answered strongly agree or agree were grouped together.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were provided the statements in column 1 prior to starting the course . They were asked to answer on a 5 point scale from strongly agree (1) to strongly disagree (5). Those who answered strongly agree or agree were grouped together.…”
Section: Resultsmentioning
confidence: 99%
“…As our understanding of functional and surgical pelvic anatomy evolves, there has been a recent trend towards post-graduate laparoscopic training courses and mini-residencies 5 . These courses address training of normal anatomy and also topics such as surgical complications, which cannot be routinely practiced in live patients 6 , hysterectomies, lymph node biopsies 7 , and dissection of neurovascular bundles 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence to suggest that robotic skills will stabilize after a substantial allowance for adaptation through an ample learning curve [10] [11]. The Training group was created to minimize variability in robotic-assisted surgery data that would be eliminated through experience with the technique.…”
Section: Methodsmentioning
confidence: 99%
“…Torricelli et al (2016), in their review article, suggested that a short period of training with laparoscopic stimulators improves laparoscopic surgical skills. Also, the authors suggest that the best way for the dissemination of laparoscopic surgery is the induction of laparoscopic simulators in the training of residents in surgery (118). Moreover, Papanikolaou et al (2019) suggested that teaching hospitals should introduce training programs using laparoscopic simulators with standardized and reproducible tasks in order to achieve better patient care with safety, efficiency and lower cost (119).…”
Section: Evidence For Training With Laparoscopic Simulation In Laparomentioning
confidence: 99%